Aging Reduces L-Type Calcium Channel Current and the Vasodilatory Response of Small Mesenteric Arteries to Calcium Channel Blockers - Albarwani, Sulayma A.; Mansour, Fathi; Khan, Abdul Aleem; Al-Lawati, Intisar; Al-Kaabi, Abdulla; Al-Busaidi, Al-Manar; Al-Hadhrami, Safa; Al-Husseini, Isehaq; Al-Siyabi, Sultan; Tanira, Musbah O. (Frontiers in Physiology, 2016)
Calcium channel blockers (CCBs) are widely used to treat cardiovascular disease (CVD) including hypertension. As aging is an independent risk factor for CVD, the use of CCBs increases with increasing age. Hence, this study was designed to evaluate the effect of aging on the sensitivity of small mesenteric arteries to L-type voltage-gated calcium channel (LTCC) blockers and also to investigate whether there was a concomitant change in calcium current density. Third order mesenteric arteries from male F344 rats, aged 2.5–3 months (young) and 22–26 months (old) were mounted on wire myograph to measure the tension during isometric contraction. Arteries were contracted with 100 mM KCl and were then relaxed in a cumulative concentration-response dependent manner with nifedipine (0.1 nM–1 μM), verapamil (0.1 nM–10 μM), or diltiazem (0.1 nM–10 μM). Relaxation-concentration response curves produced by cumulative concentrations of three different CCBs in arteries of old rats were shifted to the right with statistically significant IC50s. pIC50 ± s.e.m: (8.37 ± 0.06 vs. 8.04 ± 0.05, 7.40 ± 0.07 vs. 6.81 ± 0.04, and 6.58 ± 0.07 vs. 6.34 ± 0.06) in young vs. old. It was observed that the maximal contractions induced by phenylephrine and reversed by sodium nitroprusside were not different between young and old groups. However, Bay K 8644 (1 μM) increased resting tension by 23 ± 4.8% in young arteries and 4.7 ± 1.6% in old arteries. LTCC current density were also significantly lower in old arteries (−2.77 ± 0.45 pA/pF) compared to young arteries (−4.5 ± 0.40 pA/pF); with similar steady-state activation and inactivation curves. Parallel to this reduction, the expression of Cav1.2 protein was reduced by 57 ± 5% in arteries from old rats compared to those from young rats. In conclusion, our results suggest that aging reduces the response of small mesenteric arteries to the vasodilatory effect of the CCBs and this may be due to, at least in part, reduced current density of LTCC.